Paternal Leave and Father-Infant Bonding: Findings From the Population-Based Cohort Study DREAM - Schaber, Ronja; Kopp, Marie; Zähringer, Anna; Mack, Judith T.; Kress, Victoria; Garthus-Niegel, Susan (Frontiers in Psychology, 2021)
Background: Father-infant bonding is important for child development. Yet, in contrast to mother-infant bonding, little is known about factors that might facilitate father-infant bonding. With new generations of fathers being more involved in childcare, this study aims to examine the impact of paternal leave duration on father-infant bonding, and whether this relation is mediated by the amount of time fathers actively spend on childcare. Methods: Data of n = 637 fathers were derived from the German population-based cohort study “Dresden Study on Parenting, Work, and Mental Health” (DREAM). Mediation analyses were conducted. Duration of paternal leave (predictor), weekly hours spent on childcare (mediator), and father-infant bonding (outcome) were measured at 14 months postpartum. The potential confounders current status of paternal leave, part-time work during paternal leave, duration of solo paternal leave, age, education, and partnership satisfaction were included in a second mediation analysis. Results: Without considering confounders, duration of paternal leave positively predicted father-infant bonding through weekly hours spent on childcare. When adding confounders to the model, this indirect path did not stay significant. Moreover, in the adjusted model and on the direct path duration of paternal leave negatively predicted father-infant bonding. Additionally, partnership satisfaction positively predicted father-infant bonding. Some study variables were significantly associated with the mediator. Longer duration of paternal leave, currently being on paternal leave, younger age, and lower educational level predicted more weekly hours spent on childcare. Conclusions: Duration of paternal leave not being a stable predictor for father-infant bonding suggests that fathers, who do not have the opportunity to take long periods of paternal leave, can still form strong bonds with their infants. Other factors, for example partnership satisfaction, which might represent fathers’ underlying capacity to bond, might be more crucial for father-infant bonding. At the same time, results should not be interpreted in a way that father involvement (e.g., paternal leave/time spent) does not matter for children’s development. The finding that longer duration of paternal leave increases weekly hours spent on childcare supports the idea that facilitating father involvement can be achieved by paternal leave incentives such as non-transferable father months.